2022
DOI: 10.2147/jmdh.s364324
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Profiles of Bacteria Isolated from Hotspot Environments in Bahir Dar City, Northwestern Ethiopia

Abstract: Background Wastes generated from hotspot environments contain a wide range of antibiotics and pathogens that play a significant role in the dissemination of antibiotic-resistant bacteria in the environment. This study was carried out to isolate bacteria from hotspot environments and determine their resistance profiles to commonly used antibiotics in Bahir Dar city, Ethiopia. Methods A cross-sectional study was conducted from October 2020 to June 2021 in Bahir Dar City. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our result showed that all antibiotics were 100% resistant against Staphylococcus spp., represented in Figures 4, 5C. Similarly, Farooq et al (Geta and Kibret, 2022)…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Our result showed that all antibiotics were 100% resistant against Staphylococcus spp., represented in Figures 4, 5C. Similarly, Farooq et al (Geta and Kibret, 2022)…”
Section: Resultssupporting
confidence: 55%
“…Our result showed that all antibiotics were 100% resistant against Staphylococcus spp., represented in Figures 4 , 5C . Similarly, Farooq et al ( Geta and Kibret, 2022 ) identified Bacillus spp., Klebsiella spp., Coccobacilli , Staphylococcus spp., and Enterobacter spp. Unidentified Bacilli , Diplococcus spp., Micrococcus spp., Streptobacillus spp., and Shigella spp.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…To further complicate the problem, numerous reports have shown that enteric bacterial pathogens are resistant to multiple antibiotics enteric bacterial pathogens have been widely reported to demonstrate resistance to several antibiotics. Some bacteria pathogens with highest level of resistance were isolated from environment, surface water which serves as the main reservoir of antibiotics and antibiotic-resistant https://scientifica.umyu.edu.ng/ Gugu et al, /USci, 2(3): 009 -014, September 2023 bacteria in the environment (Chaitanand et al, 2010;Verma et al, 2011;Sharma & Rai, 2012;Geta and Kibret, 2022). Antimicrobial resistance remains a global problem (Poonia et al, 2014), and it has been 20 years of increased antimicrobial resistance since it was reported (Kapil, 2004).…”
Section: Introductionmentioning
confidence: 99%